2011
DOI: 10.1002/cjoc.201180262
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Regiochemistry of 1,3‐Dipolar Cycloaddition of C,N‐Diphenyl Nitrone with Some Vinyl Sulfoximines as Dipolarophile: Theoretical Studies

Abstract: The regiochemistry of 1,3-dipolar cycloaddition reactions of C,N-diphenyl nitrone with some vinyl sulfoximines as dipolarophile was investigated using density functional theory (DFT)-based reactivity indexes and activation energy calculations at B3LYP/6-31G(d) level of theory. Analysis of the geometries and bond orders (BOs) at the TS structures associated with the different reaction pathways shows that these 1,3-dipolar cycloaddition reactions occur via an asynchronous concerted mechanism. Analysis of the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…1,3-Dipolar cycloaddition (1,3-DC) of unsaturation (ene) to a nitrone is a powerful tool for the synthesis of five-membered heterocycles containing an isoxazole structure [3 -6]. The 1,3-DC reaction is a pericyclic reaction [7] in which 1,3-dipoles and dipolarophiles combine to generate five-membered rings [8]. For the first time in 1960, Huisgen et al [9,10] introduced the concept of 1,3-DC reactions.…”
Section: Introductionmentioning
confidence: 99%
“…1,3-Dipolar cycloaddition (1,3-DC) of unsaturation (ene) to a nitrone is a powerful tool for the synthesis of five-membered heterocycles containing an isoxazole structure [3 -6]. The 1,3-DC reaction is a pericyclic reaction [7] in which 1,3-dipoles and dipolarophiles combine to generate five-membered rings [8]. For the first time in 1960, Huisgen et al [9,10] introduced the concept of 1,3-DC reactions.…”
Section: Introductionmentioning
confidence: 99%
“…8 Experimentally; it has been found that the cycloaddition reactions of nitrilimines 1a-c with E-3-(dimethylamino)-1-(10H-phenothiazin-2-yl) prop-2-en-1-one 2 give preferentially the cycloadducts 3a, 3b and 3c respectively, shown in Scheme 1. 9 In continuation of our studies on the mechanism and regioselectivity of the1,3-DC reactions, [10][11][12][13][14][15][16][17][18] we became interested in the above mentioned reactions based on activation energy calculations, the distortion/interaction model and DFT-based reactivity indexes.…”
Section: Introductionmentioning
confidence: 99%